Assessment of Subsurface Conditions in a Coastal Area of Lagos using Geophysical Methods - K. F. Oyedele; S. Oladele; C. Okoh (Nigerian Journal of Technological Development, 2015)
An integrated geophysical and geotechnical survey was carried out at Magodo Estate, Lagos, Nigeria. The buildings in this area are either sinking or intensively affected by severe cracks showing structural instability. The survey was aimed at characterizing the shallow subsurface in order to delineate features that may have caused structural instability that led to cracking and sinking of the residential buildings in the area. To image the subsurface, resistivity profiling (2-D) using a Wenner array and Cone Penetration Test (CPT) was carried out on five profiles of length 180 m each. The acquired data were processed and interpreted integrally to image the shallow geotechnical setting of the site. Integrated interpretation led to the delineation of low resistivity, low bearing capacity clay which is identified as the main cause of instability that resulted in potentially dangerous cracking and sinking of residential buildings in the area.